Prevalence and antimicrobial resistance profiles of bacteria isolated from the urine of dogs in Ibadan, Nigeria (2019)
Bacteria exist as part of thè norma! flora of thè urogenital tract of animals. However, some of them may cause severe opportunistic infections in immuno-suppressed host requiring antimicrobial chemotherapy. Antìmicrobial resistance may lead to therapy fatture and protracted tllnesses. This study investigated thè diverse reservoirs of antimicrobial resistant bacteria in thè urogenital tract of dogs in lbadan. A total of 114 urine samples from male (42) and female (72) dogs were examined for thè presence of bacteria by inoculation onto cultural media. Bacteria identification was based on cultural, microscopie and biochemical characteristics. Bacteria isolates were tested for susceptibility to amoxicillin, amoxillin/ clavulanic acid, cefixime, ceftazidime, cefuroxime, ciprofloxacin, ampicillin/cloxacillm, erythromycin, gentamicin, nitrofurantoin, ofloxacin, perfloxacin, ceftriaxone, streptomycin, trimethoprim/sulfamethozoJeand cefuroxime. Overall, 184 bacteria isolates were identified from thè 64 (56.14%) of thè 114 urine samples examined. The remaining 47 (41.2%) of 114 samples did notyield significant bacterial growth on thè various bacteriological media. The bacteria detected in thè urine samples inciuded Escherìchia coli (59); Staphylococcvs aureus (40), Slreptococci spp (32), Klebsiella spp (22), Pseudomonas aemgìnosa (12), coagulase negative staphylococcus spp (7), Enterobacter spp (7) and Proteus mirabilis (5). The organisms showed varying degrees of susceptibility to antimicrobial agents. Many of thè organisms demonstrated resistance to at least three antimicrobials from different classes. Forty-twò resistance groups were observed among thè Gram-positive bacterial isolates while eleven resistance groups were observed among thè Gram-negative isolates. ‘APX-CRX-AM-CET-S-SXT-E-PEF-CN’ and ‘CAZ-CPR-NITAUG-OFL-CXM-GENV CRX ’ were thè predom inant resistant pattems for Gram-positive and Gram-negative isolates respectively. This study revealed a diversity and high level of multidrug resistance bacteria in thè urogenital traets of dogs. These bacteria maybe important as primary or opportunistic aetiological agents of infection in die affected host with thè possibility of zoonotic transmission to human companions.